2014
DOI: 10.1186/1746-6148-10-144
|View full text |Cite
|
Sign up to set email alerts
|

Understanding human – bat interactions in NSW, Australia: improving risk communication for prevention of Australian bat lyssavirus

Abstract: BackgroundAustralian bat lyssavirus (ABLV) infects a number of flying fox and insectivorous bats species in Australia. Human infection with ABLV is inevitably fatal unless prior vaccination and/or post-exposure treatment (PET) is given. Despite ongoing public health messaging about the risks associated with bat contact, surveillance data have revealed a four-fold increase in the number of people receiving PET for bat exposure in NSW between 2007 and 2011. Our study aimed to better understand these human – bat … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
31
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(31 citation statements)
references
References 29 publications
0
31
0
Order By: Relevance
“…Given the considerable proportion of people (approximately a quarter) in the community who reported an intention to handle injured or trapped bats [20], public health interventions should adopt multiple strategies, including: 1) communicating the risk messages to the general public that they may harm the bat and put themselves at risk of contracting the fatal ABLV infection if they attempt to rescue/handle the animal [21], because an untrained person is highly likely to be injured when handling a bat, and the bat involved in human injury will be euthanised for ABLV testing. 2) advising the public to take an alternative action when encountering injured/trapped bats; for example, contacting animal rescue groups (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Given the considerable proportion of people (approximately a quarter) in the community who reported an intention to handle injured or trapped bats [20], public health interventions should adopt multiple strategies, including: 1) communicating the risk messages to the general public that they may harm the bat and put themselves at risk of contracting the fatal ABLV infection if they attempt to rescue/handle the animal [21], because an untrained person is highly likely to be injured when handling a bat, and the bat involved in human injury will be euthanised for ABLV testing. 2) advising the public to take an alternative action when encountering injured/trapped bats; for example, contacting animal rescue groups (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…This is comparable to other studies including a study that found 84% of preventable exposures in NSW residents between 2007 and 2011 (Kardamanidis, Cashman, & Durrheim, 2013) and 60% of preventable exposures in QLD between 2009 and 2014 reported rescuing a trapped or injured bat (Si et al., 2016). A study on risk perception of the general public in NSW found that a combination of low awareness of the seriousness of ABLV combined with a desire to help injured animals resulted in high numbers of people who said they would touch a bat and place themselves at risk of ABLV (Quinn et al., 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Within Australia, this species has primarily been associated with the transmission of viral pathogens such as Hendra and Lyssavirus. However, bacterial pathogen carriage, particularly within faecal deposits, has been relatively overlooked [ 70 , 71 ].…”
Section: Discussionmentioning
confidence: 99%